A Study of the Knowledge and Practice Regarding Menstrual Hygiene in Rural Adolescent School Going Girls in an Indian Cosmopolitan City - Hossain, Samar; Sharma, Priyanka; Sen, Vandna (Journal of Pharmacy Practice and Community Medicine)
Objective: To study the knowledge and practice regarding menstrual hygiene in rural adolescent school going girls of Achrol, Jaipur- Rajasthan. Methods and materials: It is a cross-section school based study on adolescent girls between the ages of 10-19 years of age. The study period of data collection from January 2015 to June 2016. Sampling technique: Descriptive type of observational study. Sample size: 400 adolescent school girls. Statistical measures: percentages and proportions. Results: Out of the total 400 adolescent girls, it was found that majority of the girls i.e. 85.5% were using sanitary pads, most of them belonged to middle income group. Cleaning of genitals after urination and changing pads was seen in 73.5% and 73.2% of the adolescent girls respectively. 85.5% of the girls disposed their pads in the dustbin. However there were 14.5% girls who used cloth during menstruation and washed and reused it. Conclusion: Almost 90% i.e. 85.5% of the adolescent girls used sanitary pads instead of cloth and at least 75% i.e. 73.5% practiced cleaning of genitals after urination. Though a majority of the girls were aware of the use of proper menstrual absorbent and the proper disposal of the used pads, still proper training and health education (by family members, teachers, health educators and media) should be imparted so that there won’t be any misconception regarding menstrual hygiene amongst the adolescent girls.
Keywords: Knowledge And Practice; Adolescent Girls; Menstrual Hygiene; Practices; Rural India